End-User Patent Searching Using Open Access Sources. - Pat LaCourse (Issues in Science and Technology Librarianship)
Researchers can learn effective searching at their desktop and download files for immediate use. Students can learn about a particular field for program and career choices. Those seeking a job can do background checking on industry trends, individual company research, and watch a technology as it moves among companies, inventors, and locations. Because gathering information from patents is more important than ever, this paper focuses on free access points, and demonstrates comprehensive U.S. patent searching, using approaches not available via keyword terms. Other countries are developing quickly and many find that it is expedient to file international patents, so this type of searching is covered as well. [ABSTRACT FROM AUTHOR]